Comparison of hybrid 18F.fluorodeoxyglucose positron emission tomography/magnetic resonance imaging and positron emission tomography/computed tomography for evaluation of peripheral nerve sheath tumors in patients with neurofibromatosis type 1 - Raad, Roy A.; Lala, Shailee; Allen, Jeffrey C.; Babb, James; Mitchell, Carole Wind; Franceschi, Ana M.; Yohay, Kaleb; Friedman, Kent P. (World Journal of Nuclear Medicine, 2018)
Rapidly enlarging, painful plexiform neurofibromas (PN) in neurofibromatosis type 1 (NF1) patients are at higher risk for harboring a malignant peripheral nerve sheath tumor (MPNST). Fludeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) has been used to support more invasive diagnostic and therapeutic interventions. However, PET/CT imparts an untoward radiation hazard to this population with tumor suppressor gene impairment. The use of FDG PET coupled with magnetic resonance imaging (MRI) rather than CT is a safer alternative but its relative diagnostic sensitivity requires verification. Ten patients (6 females, 4 males, mean age 27 years, range 8–54) with NF1 and progressive PN were accrued from our institutional NF Clinic. Indications for PET scanning included increasing pain and/or progressive disability associated with an enlarging PN on serial MRIs. Following a clinically indicated whole?body FDG PET/CT, a contemporaneous PET/MRI was obtained using residual FDG activity with an average time interval of 3-4 h FDG?avid lesions were assessed for both maximum standardized uptake value (SUVmax) from PET/CT and SUVmax from PET/MR and correlation was made between the two parameters. 26 FDG avid lesions were detected on both PET/CT and PET/MR with an accuracy of 100%. SUVmax values ranged from 1.4–10.8 for PET/CT and from 0.2?5.9 for PET/MRI. SUVmax values from both modalities demonstrated positive correlation (r = 0.45, P < 0.001). PET/MRI radiation dose was significantly lower (53.35% ± 14.37% [P = 0.006]). In conclusion, PET/MRI is a feasible alternative to PET/CT in patients with NF1 when screening for the potential occurrence of MPNST. Reduction in radiation exposure approaches 50% compared to PET/CT.
Keywords: Neurofibromatosis type 1; peripheral nerve sheath tumor; positron emission tomography/magnetic resonance